Mechanochemical synthesis of amide functionalized porous organic polymers - Rajput, Lalit; Banerjee, Rahul (Crystal Growth & Design, 2014)
Two porous organic polymers decorated with the amide functionality were synthesized mechanochemically and their properties were compared with the ones prepared by conventional solution mediated method. All the POPs were subjected to gas and water vapor sorption studies. The mechanochemically synthesized POPs have less surface area and show moderate adsorption properties compared to the solution mediated POPs. The amide based POPs show remarkable stability in water and concentrated acids.